Diversity and Activity of Lysobacter Species from Disease Suppressive Soils - Gómez Expósito, Ruth; Postma, Joeke; Raaijmakers, Jos M.; De Bruijn, Irene (Frontiers in Microbiology, 2015)
The genus Lysobacter includes several species that produce a range of extracellular enzymes and other metabolites with activity against bacteria, fungi, oomycetes, and nematodes. Lysobacter species were found to be more abundant in soil suppressive against the fungal root pathogen Rhizoctonia solani, but their actual role in disease suppression is still unclear. Here, the antifungal and plant growth-promoting activities of 18 Lysobacter strains, including 11 strains from Rhizoctonia-suppressive soils, were studied both in vitro and in vivo. Based on 16S rRNA sequencing, the Lysobacter strains from the Rhizoctonia-suppressive soil belonged to the four species Lysobacter antibioticus, Lysobacter capsici, Lysobacter enzymogenes, and Lysobacter gummosus. Most strains showed strong in vitro activity against R. solani and several other pathogens, including Pythium ultimum, Aspergillus niger, Fusarium oxysporum, and Xanthomonas campestris. When the Lysobacter strains were introduced into soil, however, no significant and consistent suppression of R. solani damping-off disease of sugar beet and cauliflower was observed. Subsequent bioassays further revealed that none of the Lysobacter strains was able to promote growth of sugar beet, cauliflower, onion, and Arabidopsis thaliana, either directly or via volatile compounds. The lack of in vivo activity is most likely attributed to poor colonization of the rhizosphere by the introduced Lysobacter strains. In conclusion, our results demonstrated that Lysobacter species have strong antagonistic activities against a range of pathogens, making them an important source for putative new enzymes and antimicrobial compounds. However, their potential role in R. solani disease suppressive soil could not be confirmed. In-depth omics'–based analyses will be needed to shed more light on the potential contribution of Lysobacter species to the collective activities of microbial consortia in disease suppressive soils.